THE ROLE OF RUSSIAN DIPLOMACY IN THE CONSTRUCTION OF "ELECTRONIC GOVERNMENT" IN RUSSIA - D. L. Sivovolov (Vestnik MGIMO-Universiteta)
The article reviews the current challenges to international efforts invested in solving information inequality. It dwells on issues of Russian role in these efforts and the protection of Russian intellectual property and information resources, development of "electronic government" in Russia, and the role of the Russian diplomacy in preventing the adverse effects of information revolution.Author believes that the Russian diplomacy faces today a new challenge – nurturing the international environment conducive to goals of socio-economic development and preserving national sovereignty under the conditions of transnational information flows. The author singles out three main approaches to Internet governance: the U.S., Russian and the EU. U.S. states the principle of state non-intervention in Internet. Russia takes the opposite position – state intervention on legal basis. The E.U. occupies the middle ground of “smart state intervention”, which is closer to the Russian position. There multiple variations of these three positions stemming from state information dictatorship to information neoliberalism. The author states three main strategic goals of the Russian diplomacy in information sphere: – partaking in shaping international information legislation which is prone to many problems today. – protecting IT sector of the Russian economy with TNCs enjoying almost monopoly on international IT market.